Biomimetic Concealing of PLGA Microspheres in a 3D Scaffold to Prevent Macrophage Uptake. Issue 11 (21st January 2016) - Minardi, Silvia; Corradetti, Bruna; Taraballi, Francesca; Sandri, Monica; Martinez, Jonathan O.; Powell, Sebastian T.; Tampieri, Anna; Weiner, Bradley K.; Tasciotti, Ennio
Abstract : Scaffolds functionalized with delivery systems for the release of growth factors is a robust strategy to enhance tissue regeneration. However, after implantation, macrophages infiltrate the scaffold, eventually initiating the degradation and clearance of the delivery systems. Herein, it is hypothesized that fully embedding the poly(d, l ‐lactide‐ co ‐glycolide acid) microspheres (MS) in a highly structured collagen‐based scaffold (concealing) can prevent their detection, preserving the integrity of the payload. Confocal laser microscopy reveals that non‐embedded MS are easily internalized; when concealed, J774 and bone marrow‐derived macrophages (BMDM) cannot detect them. This is further demonstrated by flow cytometry, as a tenfold decrease is found in the number of MS engulfed by the cells, suggesting that collagen can cloak the MS. This correlates with the amount of nitric oxide and tumor necrosis factor‐α produced by J774 and BMDM in response to the concealed MS, comparable to that found for non‐functionalized collagen scaffolds. Finally, the release kinetics of a reporter protein is preserved in the presence of macrophages, only when MS are concealed. The data provide detailed strategies for fabricating three dimensional (3D) biomimetic scaffolds able to conceal delivery systems and preserve the therapeutic molecules for release. Abstract : To avoid clearance of drug delivery systems from 3D scaffolds, a novel biomimetic approach is proposed. A "concealing" strategy is developed, by cloaking poly(lactic‐ co ‐glycolic acid) microspheres with the type I collagen matrix of a 3D scaffold. This preserves the release kinetics of the bioactive molecules, controlling the production of inflammatory mediators.